Mohd. Kamal Hassan’s Concept and Framework of Islamization of Knowledge - Nabil Amir, Ahmad; Abdul Rahman, Tasnim (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2025)
The paper examines the idea of Islamization of human knowledge as formulated by Mohd. Kamal Hassan (1942-2023). It aims to survey its thoughtful and lasting impact as reflected in the context of his inspiring moral, spiritual, and religious ideals that influence intellectual tradition and metaphysical consciousness and the contemporary landscape of educational policy and practice in Malaysia. The philosophy and conceptual framework of Islamization of knowledge he developed was realized in the curriculum and policies of the International Islamic University Malaysia, whose structural formation and ideology were enshrined in the University’s constitution since its establishment in 1983. The study is based on a qualitative method in the form of a literature review and documentary survey. The data were scientifically analyzed using descriptive, analytical, historical, and synthesis frameworks to make an objective and accurate finding. The finding shows that Kamal has made a significant and influential impact in gearing the ideas of the tawhid worldview through his inspiring works that planned and implemented the principle of Islamization of knowledge in Malaysia. The study contributes to highlighting his consequential and unprecedented concept and holistic approaches in introducing a comprehensive theory and values of tawhid and its cultural manifestation through the theory of Islamization (Islamiyyatul ma‘rifat), integration of knowledge and values (takamul al-ma‘rifi), comprehensive excellence and Islamicization that help to reset the current context and progress of education and intellectual life in Malaysia